Optimizing Generating Unit Scheduling for Emission Reduction ‎in Thermal Power Stations with Integrated Solar Energy ‎Systems - Rathod, Mihirkumar C.; Vyas, Sanjay R. (International Journal of Basic and Applied Sciences, 2025)
Air pollution control from thermal power stations (TPS) is achieved by minimizing flue gases emission. There are many optimization ‎techniques which can be used towards effective emission reduction, but these techniques may often require additional arrangement or ‎devices. This study presents an alternative approach to emissions minimization by scheduling generating units in a strategic manner without ‎the need to add extra equipment. Increasingly expensive fossil fuels and the improving technology for renewable energy can be picked up ‎by solar energy systems to reduce emissions. In this paper, the question of generating unit schedule for a TPS with integrated solar energy ‎‎(SE) systems in order to reduce emissions is addressed. Thus, load dispatch scheduling associated with solar energy can decrease overall ‎emissions with the same power output. The schedule is optimized to account for uncertainties to manage the challenge of predicting real ‎power consumption to improve emission reduction under changing conditions. In the study, reduction of NOx, SO2, and CO2 emissions is ‎evaluated using evolutionary programming. Results show that by adding solar energy systems into the mix, better emission reductions can ‎be achieved compared to the conventional TPS systems alone. In particular, there are major reductions in NOx, SO2, and CO2 emissions ‎when solar energy is combined with marginal adjustments in the generation schedule. Furthermore, the approach enables the understanding ‎of cost consequences from generating unit scheduling. All in all, the proposed method makes TPS operations more efficient by improving ‎environmental benefits‎.